2021
DOI: 10.25259/ijdvl_431_19
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutics of xeroderma pigmentosum: A PRISMA-compliant systematic review

Abstract: Xeroderma pigmentosum is a rare hereditary autosomal recessive genodermatosis. At present, there are many treatment options for xeroderma pigmentosum, covering medical/procedural, surgical and combined modalities. However, the quality of these interventions has not been assessed. Our study aimed to perform a systematic review of the literature regarding the treatment of xeroderma pigmentosum. Multiple medical databases were accessed with the Medical Subject Headings terms; “xeroderma pigmentosum,” “therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…If this pathway is defective, this predisposes to cancer. Only very few therapeutic possibilities are available for these diseases (de Andrade et al, 2021) (Weon and Glass, 2019). Screening of a library comprising Food and Drug Administration (FDA)-approved drugs has shown that the sulfonylureas acetohexamide and glimepiride are able in vitro to enhance viability in XPA cells after UV radiation at rather high dosages (Mazouzi et al, 2017).…”
Section: Interfering With the Pathophysiological Pathways Disturbed By The Mutated Gene Intervening In Disease Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…If this pathway is defective, this predisposes to cancer. Only very few therapeutic possibilities are available for these diseases (de Andrade et al, 2021) (Weon and Glass, 2019). Screening of a library comprising Food and Drug Administration (FDA)-approved drugs has shown that the sulfonylureas acetohexamide and glimepiride are able in vitro to enhance viability in XPA cells after UV radiation at rather high dosages (Mazouzi et al, 2017).…”
Section: Interfering With the Pathophysiological Pathways Disturbed By The Mutated Gene Intervening In Disease Pathwaysmentioning
confidence: 99%
“…The most essential action of MSCs is likely the secretion of anti-inflammatory agents, whereas they may also differentiate into fibroblasts and keratinocytes. Transplanted patients are able to receive skin grafts from the same donor, which survive for long periods and outgrow into adjacent wounds, thereby suggesting immune tolerance and outgrowth of stem cells ( Ebens et al, 2020 ).…”
Section: Restoring the Underlying Gene Defect/productmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, no evidence against the use of T4N5 liposomal formulations have been reported. In particular, acute and chronic safety tests have been performed in both mice and humans, demonstrating that no adverse reactions or significant alterations in skin biology are induced by Dimericine [84,194].…”
Section: Liposomal Formulations As Nanocarriers For Dna Repair Enzymesmentioning
confidence: 99%